The challenges for the effectiveness of environmental governance at the municipal level in cities in the Amazon: articulation, implementation of public policies and the role of the State (Research, Society and Development, 2022)
This article aims to present a diagnosis of Municipal Environmental Governance carried out from the assessment of managers in the municipalities of Apuí, Boca do Acre, Lábrea and Manaus, Amazonas, based on data collected via Google Forms. There were 26 open questions, which sought to identify: the role of institutions in the implementation of public policies; environmental activities carried out by them; participation in the Municipal Environment Council; identification of organizations that make up governance and local governance; proposed actions to improve governance and environmental governance; interaction for environmental decision making; social and private sector participation; transparency and environment structure; effectiveness and efficiency in local governance and implementation of the local Agenda 21. From the construction of this scenario, the main challenges for the effectiveness of Local Environmental Governance were identified and evaluated, namely: the need to strengthen the integration between Municipalities, State and Civil Society, as the spaces for discussion are limited, there is little continuity of actions, and they do not involve actors from representative organizations or segments; the need for institutional strengthening of the municipal environmental agency; greater availability of resources for investment in institutional projects and institutional strengthening; the need to train those involved in Environmental Governance and to expand and strengthen the insertion of civil society representatives in decision-making spaces. The indicators revealed how fragile the environmental management instruments are, especially for those municipalities (Apuí, Lábrea and Boca do Acre) located in the arc of deforestation in the Amazon.